Evaluation of the virtual cement gap parameter of different CAD software programs in designing a single crown restoration: An in vitro study. - Sarhan, Moamen Mohsen; Khamis, Mohamed Moataz; Abdelhamid, Ahmed Mohamed; Ezzelarab, Salah (Journal of Prosthetic Dentistry, 2023)
The accuracy of different virtual cement gap parameters in designing a single crown in a computer-aided design (CAD) software program is still unclear. The purpose of this in vitro study was to evaluate and compare the virtual cement gap settings of 3 different CAD software programs used to design a single crown restoration. Three different CAD software programs (exocad, Dental System, and B4D) were evaluated for designing single crowns with similar virtual cement gap settings. Three experimental groups were created based on the CAD software program used (n=10). Three-dimensional analysis software program was used to assess the virtual cement gap in the CAD restoration. The Shapiro–Wilk test of normality was used. Comparisons were carried out by using 1-way ANOVA and the Scheffé post hoc test (α=.05). The Dental System software program had the lowest statistical mean error values at both tooth margin (4.6 μm) and axial wall (1.5 μm), followed by B4D then exocad. At the occlusal surface, the lowest statistical mean error value of 5 μm was achieved by the Dental System followed by exocad then B4D. Accuracy of the virtual cement gap parameter in single crown design varies based on the CAD software used. The highest accuracy was attained by the Dental System software program at all tooth surfaces, followed by B4D at the tooth margin and axial wall and by exocad at the occlusal surface.